A Collaborative Autoethnography on Being Preservice English Language Teachers Throughout the Bachelor's Degree - Cristian Camilo Peynado; María Camila Morales-Triviño; Jairo Enrique Castañeda-Trujillo (Universidad Nacional de Colombia, 2022)
This article analyzes the experiences of two preservice English language teachers within their bachelor's degree and their pedagogical practicum through a collaborative autoethnography. The authors discuss their empowerment as a contributing agent to the field of English language teaching and address issues such as methodologies, mentor teachers, native speakerism, colonial ideologies, and decolonization processes. Findings suggest that preservice English language teachers should be allowed to reflect, analyze, and thus contribute to understanding the social dynamics of what it means to teach and be a language teacher. Preservice English language teachers are not passive agents but builders of knowledge, capable of transforming their vision of education, making visible the critical aspects of education, and resisting imposed colonial pedagogical processes.